2001
DOI: 10.1155/2001/941219
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of Chronic Obstructive Pulmonary Disease: A Rationale for Spirometry as a Screening Tool

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with significant morbidity and mortality. It is the fourth leading cause of death in the United States, and its impact on quality of life can be severe. The debate on spirometry as a screening tool has been raised and dropped on various occasions over the past 30 years. This paper readdresses the debate in the light of recent evidence from population studies. Spirometry is an underused, easy to perform office-based procedure that has been further facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Other studies have suggested that adults seeking treatment at PHCCs and presenting with risk factors for COPD and typical respiratory symptoms should be priority targets for screening and early intervention. (18)(19)(20) In the present study, the COPD patients with a previous diagnosis of COPD had a higher degree of obstruction, as evidenced by the FEV 1 values in percentage of predicted. This might have been due to the fact that respiratory symptoms were more common in that subgroup.…”
Section: Resultssupporting
confidence: 47%
“…Other studies have suggested that adults seeking treatment at PHCCs and presenting with risk factors for COPD and typical respiratory symptoms should be priority targets for screening and early intervention. (18)(19)(20) In the present study, the COPD patients with a previous diagnosis of COPD had a higher degree of obstruction, as evidenced by the FEV 1 values in percentage of predicted. This might have been due to the fact that respiratory symptoms were more common in that subgroup.…”
Section: Resultssupporting
confidence: 47%
“…This lack of awareness is concerning, in view of the large health burden that COPD presents to patients and society. 3,4,6,[15][16][17][18] Measures of lung function are also key elements in stratifying patients into different treatment strategies, for both COPD 6 and asthma. 19 Moreover, early COPD detection and smoking-cessation are essential to controlling disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…2 Spirometry can adequately screen high-risk individuals for silent airflow limitation, 3,15,16,18,20 -22 and numerous studies have now identified airflow limitation as strongly associated with general health status. 12,13,17 Yet public awareness and physician appreciation of this subject appears to pale in comparison to more familiar diseases such as heart disease, stroke, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of asymptomatic individuals has been criticized, leading to recent guidelines recommending against population screening for COPD (26,27). There is, however, evidence to suggest that targeted screening strategies may be useful (28)(29)(30)(31). The Canadian Thoracic Society guidelines, therefore, recommend targeted screening of patients at risk for COPD (16).…”
Section: Discussionmentioning
confidence: 99%